Paratrochammina Minutissima n.sp. in brackish, marine-derived lakes of the Vestfold Hills, East Antarctica - Gibson, JAE; Quilty, PG; Kerrie Swadling; Newman, L; Paterson, KS (2008)
Paratrochammina minutissima n. sp. is described from Abraxas and Ace Lakes in the Vestfold Hills, East Antarctica. The species is characterized by very small size (120 mm diameter), 4K chambers in the final whorl, weak adherence of particles to the tectin chamber lining and a relatively prominent proloculus. Similar species occur in the fully marine environment and often in the abyssal ocean. Subfossil tests were observed in sediment cores from Abraxas Lake and nearby Ace Lake. Apparently, living specimens also occurred in plankton samples from Abraxas Lake, possibly indicating a lifestyle partly attached to zooplankton or floating debris, or floating unattached on density surfaces within the meromictic lake. The distribution of subfossil Paratrochammina minutissima in the sediments of Ace Lake was consistent with a marine origin for the species, while the distribution in the Abraxas Lake sediment indicated that the lake might predate the last glacial maximum.